Genetic Diversity Analysis of Edel Cocoa Clones Parental Cross Using Maturase K (matK) Gene (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2018)
Economically, cacao bean products are divided into fine flavor and bulk cocoa. Fine flavor cocoa has white color beans while bulk cocoa has purple color beans. Bean color of fine-flavor cocoa beans is determined by the presence of a double recessive gene which is inherited from Criollo cocoa type. Analysis of the genetic background in this study used maturase K (matK) gene to ascertain the identity of the genotypes which will be used as a parent in crossing of fine flavor cocoa plants. The study aimed to investigate the genetic background of the promising clones that will be used as a parent in breeding program on fine flavor cocoa based on maturase K (matK) gene in order to ensure the identity of the genotype that will be used in parent crossing and it had Criollo ancestor. DNA analysis was conducted at Agency for the Assessment and Application Technology (BPPT), Serpong, West Java. DNA analysis was conducted on eight genotypes consisting of four genotypes of fine flavor cocoa (ICCRI 02, DRC 16,  PNT 16 and DR 2) and four genotypesof bulk cocoa (MCC 01, MCC 02,  sulawesi 1,  and KW 617).  The results showed that Maturase K (matK) was one of chloroplastgene which could be used to study phylogenetic and evolution on cocoa. Two primers Mac 02 and Mac 09 were used for amplification of matK gene on cocoa with a rate of homology 99-100% with position 872 bp for Mac 02 and 1153 bp for Mac 09.The results of the phylogenetic analysis showed that the cocoa genotypes would be used as parent crossing included DR 2, ICCRI 02, DRC 16, PNT 16, MCC 01, MCC 02, Sulawesi 1, KW 617 and HJ 2 tended to have ancestral Criollo as female parent.